ANALISIS KETERSEDIAAN HUNIAN MAHASISWA PADA PROSES STUDENTIFIKASI DI KAWASAN PENDIDIKAN TINGGI TEMBALANG, SEMARANG - Sekar Kharisma Ardhia Prastiwi; Santy Paulla Dewi (Jurnal Riptek, 2021)
Tembalang Higher Education Area is growing rapidly in line with the increasing number of Diponegoro University students. The development of the area and the increase of students number triggered the emergence of studentification which resulted in changes in the social, economic, cultural and physical structures. Hence, the rate of land conversion that has not been developed into built-up land, which is 31.8% of the total area where student residences are more dominant than communities’ residential. The studentification process that has been studied shows that housing demand that are not in accordance with the its availability can lead to vacant housing or a de-studentification phase which can harm the area. Therefore, this study aims to analyze the availability of student housing in the context of studentification. The research was conducted by analyzing the variable housing availability of students and using data on the type and location of student housing. The type of student housing itself is based on the theory of studentification that consist of HMO (House Multiple Occupation), PBSA (Purpose Built Student Accomodation) and Private Housing. Meanwhile, the student residential locations are grouped based on five sub-districts, namely Tembalang Village, Bulusan Village, Pedalangan Village, Sumurboto Village and Kramas Village. Data collection was carried out through field observations and through data from google maps and interviews with the owner of the student residence. The data obtained were then analyzed using quantitative methods with quantitative descriptive analysis tools and spatial analysis. The results of the analysis show that Bulusan Village has the most varied types of housing available, both HMO, PBSA, and private housing where the percentage of land area that is not built is still quite high (> 50%) and the second closest distance to the campus is after Tembalang Village. With this diversity, Kelurahan Bulusan has a high chance of being developed as a direction for residential development for students compared to Kelurahan Tembalang which is currently too congested. Thus the construction of residential spaces at KPT Tembalang afterwards can be avoided from vacant student residences or de-studentification.